2022
DOI: 10.1177/03009858221098430
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning by Nierembergia veitchii: Effects on vascular smooth muscle cells in the pathogenesis of enzootic calcinosis

Abstract: Vascular mineralization is a hallmark of enzootic calcinosis. Histopathological, ultrastructural, and immunohistochemical investigations were performed on the external carotid arteries of seven sheep naturally poisoned by Nierembergia veitchii. Histologically, moderate to marked hyperplasia of the tunica intima was observed without mineralization. The tunica media exhibited mild to severe mineralization and osteochondroid metaplasia. Sheep with enzootic calcinosis showed arterial overexpression of osteopontin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(97 reference statements)
0
2
0
1
Order By: Relevance
“…The pathogenesis of enzootic calcinosis is complex but studies demonstrated a similarity with the bone-forming process. Recently, it was demonstrated that extracellular vesicles produced by vascular smooth muscle cells are crucial for developing vascular mineralization ( Machado et al, 2022a ).…”
Section: Poisonous Plants In South Americamentioning
confidence: 99%
“…The pathogenesis of enzootic calcinosis is complex but studies demonstrated a similarity with the bone-forming process. Recently, it was demonstrated that extracellular vesicles produced by vascular smooth muscle cells are crucial for developing vascular mineralization ( Machado et al, 2022a ).…”
Section: Poisonous Plants In South Americamentioning
confidence: 99%
“…This was a study of a lifetime. In the year of his death, Severo also published a work on this subject (Machado et al 2022).…”
mentioning
confidence: 99%
“…Este foi o estudo de uma vida. No ano de sua morte, Severo também publicou um trabalho no assunto (Machado et al 2022).…”
unclassified